Prevalence Of Glaucoma Suspects Based On Iop And Optic Disc Findings Risk Factors, Early Detection. - Waseem, Muhammad; Rafiq, Muhammad; Khan, Jehanzeb; Zeeshan Tahir, Muhammad; Hamza, Syed Amir; Sultan, Maria (Journal of Neonatal Surgery, 2025)
Background: Elevated Intraocular Pressure (IOP), such as that in a glaucoma suspect, is one of the minor diagnostic criteria of the Ocular Hypertension Treatment Study (OHTS), as well as the findings of the optic disc, which points to the suspected optic disc as the overlying optic nerve head presenting signs of a head that may be blurred at the edges. OHTS suspects were also studied in the predictive value of disc and visual field abnormalities. The role of the optometrist in the minor predictive value of the disc. Objectives: To determine the prevalence of glaucoma suspects based on intraocular pressure (IOP) measurements and optic disc characteristics, and to evaluate their association with early clinical detection, demographic and systemic risk factors, and ocular findings. Methodology: This Cross Sectional Study conducted at department of Ophthalmology, Gajju Khan Medical College Swabi from jan 2023 to jan 2024.Demographic information, systemic history, and refractive data were collected in a cross-sectional study of adult patients visiting an eye clinic, with informed consent obtained. Goldmann applanation tonometry was used to measure IOP, and fundus exams were dilated to evaluate CDR asymmetry, rim thinning, and disc haemorrhages. Those who had IOP higher than 21 mmHg or had morphologies of the optic disc that were deemed suspicious were placed in the category of glaucoma suspect. Results: A total of 100 patients were examined, with a mean age of 47.2 ± 12.5 years; 55% were male. Myopia was present in 32%, diabetes in 22%, and hypertension in 28%. The prevalence of glaucoma suspects was 19% (n = 19). Mean IOP was significantly higher in suspects (23.6 ± 3.5 mmHg) than no suspects (16.2 ± 2.7 mmHg, p < 0.001). Mean CDR was also greater (0.67 ± 0.08 vs. 0.42 ± 0.10, p < 0.001). Older age (p = 0.02), myopia (p = 0.04), and family history (p = 0.03) were significantly associated. Conclusion: This outpatient population had a relatively commonality of glaucoma suspects in which specific positive correlations were exhibited regarding age, myopia and family history. High IOP levels and questionable optic disc findings remained strong predictors of risk. Prompt identification of suspects enables timely monitoring, modification of risk factors, and initiation of appropriate therapy..